Acute Effects of the Chlorpyrifos Pesticide on Common Carp (Cyprinus carpio L., 1758) - Jaffar, Noor Sadiq; Rabee, Adel M. (Iraqi Journal of Science, 2022)
In present study, an attempt has been made to investigate the effect of Chlorpyrifos insecticide on carp Cyprinus carpio L. through acute toxicity bioassay. The LC50 were estimated as 1897, 1266, 985 and 792 μg/L during 24 , 48, 72 and 96 hr. respectively by using the concentrations 500 , 1000, 1500 , 2000, 2500 and 3000 μg/L indicating high sensitivity of fish to chlorpyrifos. The behavioral response observed in the fish were erratic swimming, loss of reflex, hyperactivities, decrease in appetite secretion of mucus, increase movement of operculum and hyperventilation . These effects increased with increasing concentration of the chlorpyrifos and duration of exposure.